Fate tracing of hepatocytes in mouse liver. Issue 1 (December 2017) - Gu, Xiaowen; Huang, Danyi; Ci, Lei; Shi, Jiahao; Zhang, Mengjie; Yang, Hua; Wang, Zhugang; Sheng, Zhejin; Sun, Ruilin; Fei, Jian
Abstract Hepatocytes perform most of the functions of the liver and are considered terminally differentiated cells. Recently, it has been suggested that hepatocytes might have the potential to transdifferentiate or dedifferentiate under physiological or pathological conditionsin vivo . Epithelial-mesenchymal transition of hepatocytes in liver fibrosis has also been proposed. However, these findings have not been fully confirmed. In this study, hepatocytes were genetically labelled for cell fate tracing using lacZ via the tamoxifen-induced CreERT/loxP system. After induction with tamoxifen, alb + cells were permanently marked by lacZ expression, and all progeny lacZ + cells were derived from a single source with no interference. We did not observe transdifferentiation or dedifferentiation of hepatocytes into cholangiocytes or hepatic progenitor cells under conditions of liver homeostasis or following a 2/3 partial hepatectomy. Meanwhile, lacZ/OPN-positive cells were observed in livers of 3, 5-diethoxycarbonyl-1, 4-dihydrocollidine-fed mice, and lacZ/alpha-smooth muscle actin-positive cells were detected in carbon tetrachloride-induced chronic liver injury models. These results suggested that some existing differentiated alb + cells might have the potential of transdifferentiation/dedifferentiation or epithelial-to-mesenchymal transitionin vivo in some liver injury models, but the proportion of these alb + cells in liver was very low, and their significance and actual function during the pathological process remains to be elucidated.